2003
DOI: 10.1107/s0108270103017098
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Dinitroguanidine

Abstract: The title compound, CH(3)N(5)O(4), is almost planar, and the conformation is fixed by two intramolecular N-H...O hydrogen bonds. Owing to the delocalization of pi-electron density over the whole molecule, there is through-conjugation, with the C-N, N-N and N-O bond lengths having values intermediate between those typical for the corresponding single and double bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…According to experimental structural studies of the crystalline compounds, the tautomer containing the nitro group at the imine nitrogen atom predominates in the case of nitroguanidine [16], dinitroguanidine [17], and aminonitroguanidine [14]. In 2-(2,4,6-trinitrophenyl)guanidine, the trinitrophenyl group is also located at the imine nitrogen [18].…”
Section: Introductionmentioning
confidence: 97%
“…According to experimental structural studies of the crystalline compounds, the tautomer containing the nitro group at the imine nitrogen atom predominates in the case of nitroguanidine [16], dinitroguanidine [17], and aminonitroguanidine [14]. In 2-(2,4,6-trinitrophenyl)guanidine, the trinitrophenyl group is also located at the imine nitrogen [18].…”
Section: Introductionmentioning
confidence: 97%
“…In order to give a intuitive understanding of the nitration process of compound E1, the optimized structure of compound E1 at B3LYP/6-31G (d,p) level is also presented in Figure 8. It can be concluded that N1 and N14 are less reactive compared to that of N8 and N13 due to the space steric effect of the nitro group and intramolecular hydrogen bonds effects [30] of O7···H2 and O22···H18. Therefore, compounds E2 (ρ = 1.91 g cm -3 ; D = 9.2 km s -1 ; P = 39.2 GPa) and E3 (ρ = 1.96 g·cm -3 ; D = 9.8 km·s -1 ; P = 44.0 GPa) [31] might be possible to be synthesized rather than compounds E4-E7.…”
Section: Articlementioning
confidence: 95%
“…Comparison of NGu with various NGu-derivatives such as dinitroguanidine (7) [111], aminonitroguanidine (8) [112], diaminonitroguanidine (9) [112], N-methyl-N'-nitroguanidine [113], and 1,1,3,3-tetramethyl-2-nitroguanidine [114] shows that the bond lengths encountered before are not a singularity but common features for nitroguanidines and explain their extraordinary stability and insensitivity by push-pull electron delocalization to iminium nitronate structures (Figure 26).…”
Section: Crystal and Molecular Structurementioning
confidence: 99%